2018
DOI: 10.1097/aud.0000000000000482
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Age and Stimulus Frequency Interaction for Ocular Vestibular-Evoked Myogenic Potentials

Abstract: The results of the study showed significantly higher prevalence of frequency tuning at 1000 Hz in older adults above 60 years of age. Because the shift in frequency tuning to ≥1000 Hz is frequently used for identification of Meniere's disease, it is suggested that age-related correction be used for the diagnosis of Meniere's disease when using frequency tuning of oVEMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…Previously, Piker et al 10 demonstrated that age can have a significant effect on the tuning of VEMP, and middle-aged individuals have a shift in their best frequencies for VEMP. On similar grounds, Singh et al 15 have also reported that there is significant interaction between age and frequency tuning for oVEMP. In our study, we recruited participants aged between 19 and 59 years.…”
Section: Discussionmentioning
confidence: 72%
“…Previously, Piker et al 10 demonstrated that age can have a significant effect on the tuning of VEMP, and middle-aged individuals have a shift in their best frequencies for VEMP. On similar grounds, Singh et al 15 have also reported that there is significant interaction between age and frequency tuning for oVEMP. In our study, we recruited participants aged between 19 and 59 years.…”
Section: Discussionmentioning
confidence: 72%
“…One possible explanation for these missing oVEMPs is subject age. The oVEMP response rate decreases with age and many healthy subjects over age 60 may not have an observable oVEMP response (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…3) (Park et al, 2010, Rosengren et al, 2011, Rodriguez et al, 2019). The consequence of this is that AC oVEMPs are more often absent than cVEMPs and are particularly sensitive to the effects of age (Piker et al, 2011, Piker et al, 2013, Piker et al, 2015, Rosengren et al, 2011, Singh and Firdose, 2018). This has a significant impact on the clinical utility of the AC oVEMP to detect vestibular loss, as responses can be absent in substantial numbers of healthy older adults.…”
Section: Which Stimulus To Use? Ac Versus Bcmentioning
confidence: 99%